PEMBUATAN FILM ANIMASI 3D “BUAH TANGAN BERBUAH KENANGAN” DENGAN METODE MDLC - nurhayati, nurhayati; Azizul, Muhammad; Kurmazi, Rezi; Firdania, Milda Surgani; Sitompul, Noferianto (UNIVERSITAS STEKOM, 2023)
Sambas has a traditional craft of songket cloth known as Kain lunggi or kain Bannang ammas because the motif is woven from gold and silver colored threads. Lunggi fabric has many weaving motifs, one of the most famous weaving motifs is the motif of bamboo shoots (Pucuk Rebung). But not a few people who do not know other motifs besides woven fabrics and other information about the motif of Sambas woven fabrics that are already quite global. So it is important to convey this information to the public interestingly. One of the media that can be used is through 3D animated films. This study was conducted by applying the MDLC method in which the process of modeling, rigging texturing, editing and animating in it. Based on the test results of 2 media experts at 84%, 2 material experts at 89%, and 30 general public at 89.46%, this animated film deserves to be published with a duration of 15 minutes and mp4 format.